1990
DOI: 10.1029/jb095ib06p08809
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry of the Northern Barbados Accretionary Complex Transect: Ocean Drilling Project Leg 110

Abstract: Detailed studies of the major element geochemistry, oxygen and hydrogen isotope ratios of pore fluids, and the 87Sr/86Sr ratio of dissolved strontium have made it possible to unravel physical and chemical processes that affect the pore fluid chemistry in a transect of drill holes across the northern Barbados accretionary complex. These processes include (1) alteration of volcanic ash buried in the Pleistocene‐Pliocene sediment column; (2) alteration of underlying basalts of layer 2 of the oceanic crust; (3) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 28 publications
(5 reference statements)
4
60
0
Order By: Relevance
“…Low-chlorinity pore waters have been documented near the toe of the Barbados accretionary prism, especially in the vicinity of the basal décollement (Gieskes et al, 1990b;Shipboard Scientific Party, 1995a, 1995b. Previous investigators suggested that these pore waters evolved during smectite-to-illite reactions within deeper domains of underplating and then migrated toward the prism's toe (Gieskes et al, 1990a;Wilkens et al, 1990;Vrolijk et al, 1991).…”
Section: Thematic Backgroundmentioning
confidence: 99%
“…Low-chlorinity pore waters have been documented near the toe of the Barbados accretionary prism, especially in the vicinity of the basal décollement (Gieskes et al, 1990b;Shipboard Scientific Party, 1995a, 1995b. Previous investigators suggested that these pore waters evolved during smectite-to-illite reactions within deeper domains of underplating and then migrated toward the prism's toe (Gieskes et al, 1990a;Wilkens et al, 1990;Vrolijk et al, 1991).…”
Section: Thematic Backgroundmentioning
confidence: 99%
“…The lateral and vertical pressure gradients that are established cause fluids to be expelled locally or diffusely from the thickening section (Moore et al, 1988;Davis et al, 1990;. The rates and total volumes of fluid flow are not as great as those in axial hydrothermal systems, although thermal and particularly chemical fluxes can be locally significant (Gieskes et al, 1990;Davis et al, 1990;Langseth et al, 1990;Foucher et al, 1990), and the integrated effect of the flux of expelled fluids on the diagenesis and alteration of the sediment section is suspected to be large (Kulm and Suess, 1990;Hyndman and Davis, in press).…”
Section: Holes In Accretionary Prismsmentioning
confidence: 99%
“…More fluid is present below thrust faults penetrated at Site 829, which implies that the faults may channelize fluid flow similar to the Barbados accretionary wedge (Mascle, Moore, et al, 1988). Moreover, the deepest samples at Site 829 are characterized by low chloride and high methane concentrations, a covariance that also characterizes the pore-fluid chemistry within the décollement at the Barbados accretionary wedge (Gieskes et al, 1990). Thus, the fluid near the deep thrust fault at Site 829 may have been derived from the décollement and subduction-related processes.…”
Section: Resultsmentioning
confidence: 92%